THE EFFORTS TO SURVIVE IN RACHAEL LIPPINCOTT’S NOVEL FIVE FEET APART - Chairunnisa, Dita; Asnani, Asnani (Universitas Islam Sumatera Utara, 2025)
This study analyzed the protagonist’s survival efforts and their psychological impacts in Rachael Lippincott’s Five Feet Apart. Using a qualitative descriptive method, the research identified five key forms of survival efforts—therapy, yoga, medication, digital self-expression, and surgery—and their impacts on resilience and recovery. This study adopts qualitative method to acquire and describe the data about the main character’s efforts to survive. The discussion is divided into two topics concerned to the aspects of the analysis. The first is focused on efforts to survive of the main character then the second is about the impacts of efforts to survive of the main character. There are five efforts to survive in the novel. They are: doing therapy, doing yoga, taking medicine, creating a YouTube account, and doing surgery; The impact of effort to survive are: to relieve her breathing naturally, to increase endurance and make recovery faster and to have a good life expectancy